Radio SQ dan Pengembangan Dakwah: Studi Difusi Inovasi tentang Peran Radio SQ 104.3 FM Pangkalpinang dalam Usaha Pengembangan Dakwah Islam di Wilayah Pangkalpinang - Safril Safril (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2019)
Da'wah Islamiyah activities can be done by any method and media, including preaching by the radio. 104.3 FM SQ Radio is a kind of Da’wah Radio in the Pangkalpinang area. This radio has an important role in the effort to develop Islamic da'wah in the Pangkalpinang and Bangka Belitung regions, through its broadcast program which is divided into two forms, namely: On Air and Off Air. Referring to the theory of Innovation Diffusion, there are five important roles of SQ FM Radio in the effort to develop da'wah, namely: 1) Knowledge; 2) Persuasion; 3) Decision; 4) Implementation; and 5) Affirmation.